SISTEM PENGAMANAN DAN PENGAWASAN PENGGUNAAN GADGET BAGI ANAK USIA DINI DAN REMAJA - Anggraeni, Leni; Putri, Nabella Kusuma Maspa; Idris, Muhammad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
Gadgets are communication tools that can support all aspects of gadgets, they can also have positive and negative impacts on the development of young children and adolescents, the positive impact that children get is that they are able to access all kinds of information such as global information, educational resources to get acquainted with outsiders and others. -others, but gadgets also have a negative impact such as playing games, being able to access sites that are not for children to see. This is where the role of parents is really needed to supervise the use of gadgets for children, parents should be more extra vigilant about their children's gadget use and monitor all children's activities when using gadgets. This study aims to make parents more aware and able to monitor their children's activities when using gadgets without parental assistance, while also informing parents that they need to be more careful with their children. This study also uses Android, Website, MYSQL, PHP, and HTML in making applications that will be used. The method used in this research is a questionnaire/questionnaire method, literature study, and observation. How to improve supervision of children in the use of gadgets is to create a system that can be used to monitor their children's gadget use activities. The method of supervision with this system is by entering the name and cellphone number.